Innovative Application of BIM Based Intelligent Prefabricated Buildings in Green and Low-carbon Design - Huang, Kun (Transactions on Computer Science and Intelligent Systems Research, 2024)
This article explores the innovative application of intelligent prefabricated buildings based on BIM technology in green and low-carbon design. By analyzing the combination of BIM technology and prefabricated buildings throughout their entire life cycle of design, construction, and operation, the enormous potential of BIM technology in energy conservation, emission reduction, resource utilization efficiency improvement, and optimization of building performance has been demonstrated. Research has shown that BIM technology can effectively improve the design accuracy and construction efficiency of prefabricated buildings, reduce material waste and carbon emissions, and promote the sustainable development of the construction industry. In addition, this article also combines practical application examples to illustrate the specific application effects of BIM in intelligent prefabricated buildings, and looks forward to future development directions.